Music in childhood from preschool through the elementary grades - Campbell, Patricia Shehan; Scott-Kassner, Carol (Schirmer Cengage Learning, 2014)
As inspirational as it is informative, this text combines the best research and practical knowledge to give music education students the necessary tools to take to their future classroom. This comprehensive text presents contemporary theories and practices of music education including strategies for developing pitch, vocal, rhythmic, instrumental, listening, movement and creative responses in children. It includes chapters on multiculturalism, motivation and management, special learners, assessment, and curriculum integration and development.